The opinions of physical education teachers about the prevalence of obesity and nutrition problem in schools - Uğraş, Sinan; Sağın, Ahmet Enes; Güllü, Mehmet (Progress in Nutrition, 2020)
Purpose: In this study, it has been aimed to examine the opinions of physical education teachers about obesity and nutrition, which is a growing public health problem. Methods: 13 physical education teachers selected with maximum diversity sampling for the study constituted the sample of the study. Individual interviews were conducted by using semi-structured questionnaires in the research. As a result of the content analysis of the raw data obtained from the semi-structured interview forms, four themes were obtained. Results: These four themes are “The current state of obesity in schools and the view of physical education teachers in nutrition and obesity”, “Obesity Victim Students “reflection on Physical Education lesson”, “Studies carried out at school and the struggle of physical education teachers with malnutrition and obesity”, “The necessity of having a nutrition lesson in the curriculum. “The Future of Nutrition and Obesity” Conclusions: As a result of the research, it has been revealed that Physical Education teachers can play a role in the prevention of obesity and nutrition. However, it was concluded that physical education teachers did not have a planned and programmed strategy to prevent and reduce obesity. The Physical Education teachers who participated in the research stated that the nutrition issues were not sufficiently included in the curriculum and they suggested that they could be taught as a separate lesson.